EVALUASI KEBIJAKAN SOSIAL (STUDI PADA PROGRAM BANTUAN PANGAN NON TUNAI (BPNT) DI KOTA SERANG) (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2023)
The purpose of this study is to discuss the evaluation of social policies on the BNPT program in Serang City through an analysis of policy evaluation criteria which include the relevance of the BPNT program to needs and problems, effectiveness in producing the effects of change, efficiency in achieving goals and impacts and sustainability and long-term benefits. This research method uses a qualitative approach through interview and observation data collection techniques. Data analysis techniques used the process of data classification, labeling and categorizing based on research questions and interview transcripts for further data analysis. The results of the study show that the evaluation of social policies in the BNPT program in Serang City shows several criteria that have not been effective or successful. The level of successful evaluation is only on the relevance of the program while effectiveness, efficiency and sustainability show that it is not yet effective. Research findings show the need for intensive coordination, policy innovation in boosting community capacity and skills and the importance of community and regional characteristics in the approach of social assistance programs.